ANALISIS KUALITAS WEBSITE E-GOVERNMENT MENGGUNAKAN METODE WEBQUAL PADA PEMERINTAH DAERAH MOROWALI - Sutejo, Danang; Soedijono W A, Bambang; Sunyoto, Andi (Informasi Interaktif, 2018)
The rapid development of Internet technology helps human life in a variety of information and the use of information technology is not only used by individuals but has been used by organizations including government agencies through e-Government. Implementation of e-Government has been applied to the local government district Morowali but never done the measurement level of website quality this research using WebQual 4.0 method that includes usability quality dimensis, service quality dimensis, information quality dimensis and by adding new dimensis of user interface quality and with Importance-Performance Analysis (IPA) method.This research is expected to know the level of success of its application, knowing what dimensions need to be improved or need to be maintained and know gap / gap between perceived / performance and expectation according to user in order to achieve the quality of website desired by user. Population taken as sample of this research is society of district of Morowali which divided into 3 element that is employee, student / student and society counted 95 respondents.Overall, all dimensis have gaps or gaps in which the value of perception is smaller than the expected value so each pameter should get special attention to improving the quality of the website, especially on dimensis that fall into the category of main priority or the main concern is the movement between pages on the website quickly displayed (UQ4 ), Attractive display (UQ5), Provides relevant information (IQ4), Provides easily readable and understandable information (IQ5), Websites using appropriate fonts (UIQ2), Links on websites works well (UIQ5). Keywords: WebQual, Importance-Performance Analysis (IPA), e-Government.